Frontispiece: The Parent Cyclopentadienyltin Cation, Its Toluene Adduct, and the Quadruple‐Decker [Sn3Cp4]2+. Issue 11 (6th March 2017) - Schleep, Mario; Hettich, Clarissa; Velázquez Rojas, Jennifer; Kratzert, Daniel; Ludwig, Thilo; Lieberth, Katharina; Krossing, Ingo
Abstract : Metallocenes The half‐sandwich cation [SnCp] +, a toluene adduct thereof, and the quadruple‐decker [Sn3 Cp4 ] 2+ were synthesized and characterized as salts of weakly coordinating anions as described by I. Krossing et al. in their Communication onpage 2880 ff.